1998
DOI: 10.1183/09031936.98.12030592
|View full text |Cite
|
Sign up to set email alerts
|

Four years' experience of intravenous colomycin in an adult cystic fibrosis unit

Abstract: aa Most adult patients with cystic fibrosis (CF) are colonized with Pseudomonas aeruginosa [1] and usually require i.v. antibiotic therapy to treat pulmonary exacerbations with this organism. Strains of P. aeruginosa are showing increasing resistance to conventional antipseudomonal antibiotics [2, 3], yet despite this 98.8% are still sensitive to colomycin sulphomethate, an antibiotic which is easy to administer intravenously. Colomycin is a cationic cyclic polypeptide (sometimes known as polymixin E) isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 16 publications
1
53
0
3
Order By: Relevance
“…for 12 days resulted in an improvement of FEV 1 values by 9.2%, and therapy of patients with colistin plus another antipseudomonal agent improved lung function by 18.5% (323); in another study performed by this group, an improvement of lung function of 6.9% due to combination therapy was reported (324).…”
Section: Colistinmentioning
confidence: 99%
“…for 12 days resulted in an improvement of FEV 1 values by 9.2%, and therapy of patients with colistin plus another antipseudomonal agent improved lung function by 18.5% (323); in another study performed by this group, an improvement of lung function of 6.9% due to combination therapy was reported (324).…”
Section: Colistinmentioning
confidence: 99%
“…Virtually all patients received other antimicrobial agents, and their impact on outcomes at- (35,40,119), with particularly high success rates (ϳ85% to 95%) in treating urinary tract infections. In the late 1990s, colistimethate used in the treatment of respiratory exacerbations in patients with cystic fibrosis was reported (33,34,95). In those reports, patients with chronic bronchopulmonary infection with P. aeruginosa were given a ϳ2-week trial, with modest clinical and spirometric improvement.…”
Section: Clinical and Microbiological Outcomesmentioning
confidence: 99%
“…Approximately 2% of patients will develop allergic manifestations including fever, eosinophilia, and macular and urticarial rashes (85,95). However, the more prominent side effects involve neurotoxicity and nephrotoxicity, perhaps attributed to high binding to brain and renal tissue (91).…”
Section: Initial Toxicity Reportsmentioning
confidence: 99%
“…Efficiency has been shown at doses ranging from 1 million units twice daily [43] to 2 million units three times daily [72]. Colistin has been used with efficiency by the parenteral route in patients with multiresistant P. aeruginosa infection [73,74].…”
Section: Penetration Of Antibiotics Into Respiratory Secretions and Pmentioning
confidence: 99%
“…However, two studies reported a low frequency of nephrotoxicity [73,74]. The UK is the only known European country where colistin is given intravenously in CF patients.…”
Section: Intravenous Antipseudomonal Antibiotic Therapy In Cystic Fibmentioning
confidence: 99%